Alcohol, marijuana, and nicotine use as predictors of impaired driving and riding with an impaired driver among college students who engage in polysubstance use. (September 2021) - Hultgren, Brittney A.; Waldron, Katja A.; Mallett, Kimberly A.; Turrisi, Rob
Highlights: Using all three substances may increase odds of impaired driving behaviors. Driving under the influence may be more likely when marijuana only is used. Riding with impaired drivers may be more likely when alcohol and marijuana are used. Additional daily level assessments of impaired driving behaviors are needed. Abstract: Objective: While alcohol, marijuana, and nicotine are the most commonly used substances, there is limited research on the between- and within-person associations of their use and driving under the influence (DUI) and riding with an impaired driver (RWID). The current study utilized a burst design to assess how use and co-use of these substances is associated with DUI and RWID. Methods: College student drinkers with past-year marijuana and/or nicotine use (N = 367) were assessed on two consecutive weekends for three semesters. Logistic regression compared students who only reported drinking to student drinkers who used marijuana, nicotine, or all three substances on likelihood to DUI and RWID. Multilevel logistic models assessed the associations of varied combinations of substances with the daily likelihood of DUI and RWID. Results: Compared to students who only used alcohol, students who also reported marijuana use were more likely to DUI (OR = 5.44), and students who reported use of alcohol, nicotine and marijuana more likely to DUI (OR = 10.33) and RWID (OR = 10.22). Compared to occasions when only alcohol was used, DUI was more likely on marijuana only occasions (OR = 9.08), and RWID was more likely on alcohol and marijuana occasions (OR = 3.86). However, confidence intervals were wide for effects. Discussion: Students reporting use of all 3 substances had higher overall risk of DUI and RWID indicating prevention efforts for DUI and RWID should include all substances. Implications for prevention and intervention strategies at the individual and environmental level are discussed.